2013
DOI: 10.1186/1742-4755-10-50
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pregnancy intention on the use of antenatal care services: systematic review and meta-analysis

Abstract: BackgroundThere has been considerable debate in the reproductive health literature as to whether unintended pregnancy influences use of maternal health services, particularly antenatal care. Despite the wealth of studies examining the association between pregnancy intention and antenatal care, findings remain mixed and inconclusive. The objective of this study is to systematically review and meta-analyse studies on the association between pregnancy intention and antenatal care.MethodsWe reviewed studies report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
75
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 25 publications
17
75
1
2
Order By: Relevance
“…Facility based study in Addis Ababa has shown that women with planned pregnancies were more likely to book ANC early [22] as compared to those with unplanned pregnancies. Other studies also show that unintended pregnancies are associated with delayed initiation of antenatal care [15,16]. An urban based study in the Democratic Republic of Congo shows that women who had unplanned pregnancies were less likely to attend ANC services compared to those who had planned their pregnancies by themselves or jointly with their partners [42].…”
Section: Factors Determining the Utilisation Of Anc Servicesmentioning
confidence: 99%
“…Facility based study in Addis Ababa has shown that women with planned pregnancies were more likely to book ANC early [22] as compared to those with unplanned pregnancies. Other studies also show that unintended pregnancies are associated with delayed initiation of antenatal care [15,16]. An urban based study in the Democratic Republic of Congo shows that women who had unplanned pregnancies were less likely to attend ANC services compared to those who had planned their pregnancies by themselves or jointly with their partners [42].…”
Section: Factors Determining the Utilisation Of Anc Servicesmentioning
confidence: 99%
“…A variable for whether or not the pregnancy was intended was also included to capture the need for ANC. Previously, researchers have shown that willingness to visit healthcare professionals are higher for desired pregnancies (Dibaba, Fantahun, & Hindin, 2013).…”
Section: Independent Variablesmentioning
confidence: 99%
“…This association was evidenced by similar studies conducted in Brazil In the study conducted in three maternity hospitals in Rio de Janeiro, in 2000, the probability of women undergoing inappropriate prenatal care was twice as high for victims of PVIP during pregnancy than among women who did not report violence 9 . Women in situations of intimate partner violence tend to start prenatal care later and present lower adhesion to the program due to problems resulting from violence, such as depression during pregnancy, low self-esteem, and greater difficulty in caring for their health 32 ; that also happens because they have less partner support, including for prenatal care 33 , as evidenced in this study, or because it is an unintended pregnancy 8 . Nevertheless, it is possible that the embarrassment of exposing physical marks of violence can contribute to lower adhesion to prenatal care appointments 33 .…”
Section: Discussionmentioning
confidence: 88%
“…569/GM, Minister's Office, from December 1 st 2000) established the Program for Humanization of Prenatal Care and Childbirth (PHPN) to reduce maternal and child morbidity and mortality by improving access to as well as coverage and quality of care in prenatal, childbirth, and puerperium periods 6 . Some factors are described as associated with no prenatal care, which include belonging to social segments with lower income, having less formal education, belonging to the black race, being over 35 years old, being multiparous, having depressive symptoms during pregnancy, making abusive use of alcohol and/or illicit drugs, having unstable marital status, unintended pregnancy history, partner's dissatisfaction with pregnancy, and partner's violence [7][8][9][10][11][12][13][14] . RESUMO: Objetivo: Analisar a associação entre violência física pelo parceiro íntimo e uso inadequado da atenção pré-natal.…”
Section: Introductionmentioning
confidence: 99%